Instituting Environmental Protection: From Red to Green in Poland - Cole, Daniel H. (1998)
Under socialism, Poland suffered tremendous environmental devastation. After socialism, Poland's environmental performance has improved remarkably. This book explains that system-specific institutions of socialism undermined environmental protection by creating regulatory conflicts of interest that led the Party/state to soften budget and law constraints on polluters. Those problems have diminished in post-Communist Poland as socialist legal, political and economic institutions have been replaced by liberal-democratic institutions and competitive markets. The analysis carries important implications for an institutional theory of environmental protection.https://www.repository.law.indiana.edu/facbooks/1153/thumbnail.jp